If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 65(2x + -5) = 180 Reorder the terms: 65(-5 + 2x) = 180 (-5 * 65 + 2x * 65) = 180 (-325 + 130x) = 180 Solving -325 + 130x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '325' to each side of the equation. -325 + 325 + 130x = 180 + 325 Combine like terms: -325 + 325 = 0 0 + 130x = 180 + 325 130x = 180 + 325 Combine like terms: 180 + 325 = 505 130x = 505 Divide each side by '130'. x = 3.884615385 Simplifying x = 3.884615385
| Cos(45+x)=.42cos(45-x) | | 8(4-2.5)=16 | | 11(-3x+2)-2(1-5x)=-7x-6x | | 9(4-2n)-3=4-6(3n-5) | | 3ln(x+2)-5ln(5x)=x | | .6x+5=3 | | -5r-5(5+5r)=-5(2+7r) | | -4.0x+2.7-16x=-4.6x+2.7 | | 2x-160250-160250=320420-160250 | | x^2y-X^2+4y-9=0 | | 8+(-8)=-8-8 | | 17x-4y=29 | | -5(-3.25)=4m+8 | | (2t-5)(6t+1)=(4t-3)(3t+6) | | 2c+3=3-4 | | 4(6.25)+3k=34.60 | | 2x-23+2x-17=8 | | Z^2-(i+1)*z+i=0 | | 5x*9-7=3 | | 12-5(3(-1)+2)=17 | | 9(2n)-3=4-6(3n-5) | | 3x^2-36x-27=0 | | 4m+4+7m=13+8m | | 11(-3x-2)-2(1-5x)=-7x-6x | | 5345+n=288195 | | m+3(4)=7 | | F(-3)=2x+4 | | .66m+2=1m-3 | | 53435+n=2888195 | | 4x-2(x-4)=-7+5x-6 | | 47.39=9g+3.92 | | 6+-4+2(6)=14 |